Effect of borax application on young coconut palms - P. G. Kamalakshiamma; M. Shanavas; D. Prema; Jacob Mathew (International Coconut Community Journal, 2005)
There is increasing incidence of boron deficiency in coconut palms in the root (wilt) affected tract in the southern districts of Kerala, India. An earlier survey in this tract indicated that 19-25% of the palms had boron deficiency symptoms. The symptoms manifested due to boron deficiency in coconut palms include malformations in leaves as well as in the nuts resulting in stunted growth and low productivity. A field experiment was conducted at Central Plantation Crops Research Institute, Kayamkulam to study the effect of different doses of boron on deficiency symptoms and the nutrition of coconut seedlings. The results revealed that the seedlings which had boron deficiency symptoms showed recovery with the boron application. Among the different levels of borax (Na2B4O7.10H2O) tried on coconut seedlings, application of 300 g borax per seedling per year in two equal splits was found effective to achieve recovery and to improve the growth of the young seedlings. The seedlings treated with borax showed improvement in growth parameters such as girth at collar, annual leaf production and total functional leaves and boron content in leaf tissues.